Learning from the Past Bridging Digital and Physical Markets: A Guidelines for Future Research Agenda of Online-to-Offline (O2O) Marketing Strategy - Putra, Aditya Halim Perdana Kusuma (International Review of Management and Marketing, 2024)
This bibliometric study comprehensively analyses the scholarly landscape surrounding Online-to-Offline (O2O) commerce from 2006 to 2023. Through a systematic review of existing literature with a bibliometric analysis approach, this research identifies pivotal themes, methodologies, and findings that characterize the evolution and impact of O2O strategies across various sectors. The study begins by tracing the conceptual foundation of O2O commerce, emphasizing its role in integrating digital and physical consumer experiences in response to the changing dynamics of consumer behaviour and market demands. It highlights the strategic adoption of O2O models by e-commerce entities and brick-and-mortar stores, aiming to create a seamless shopping journey by leveraging the strengths of both online and offline platforms. The analysis focuses on the strategic implications for businesses, including the decision-making processes regarding market coverage, delivery costs, and inventory management to enhance profitability and sustainability. The research further delves into consumer behaviour, examining factors influencing the preference for online or offline purchasing, such as demographic characteristics, product types, price levels, and perceived service quality. The findings reveal a dynamic evolution of O2O strategies, underpinned by a growing emphasis on customer engagement, technological innovation, and the strategic management of online and offline synergies. The research underscores the transformative potential of O2O commerce in bridging the gap between digital and physical marketplaces, enhancing consumer experiences, and fostering sustainable business practices. In conclusion, this bibliometric study sheds light on the multifaceted dimensions of O2O commerce, offering valuable insights for academics, practitioners, and policymakers interested in the strategic integration of digital and physical retail environments. It calls for continued research and innovation to harness the full potential of O2O models in meeting the complex needs of consumers and businesses in the digital era.